Roles of metal microelements in neurodegenerative diseases - Leal, M. F. C. (2021)
Neurodegenerative diseases are characterized by a progressive loss of neuronal structures and functions. Although all biochemical and/or physiological processes are not completely understood, it is known that the main neurodegenerative diseases, like Alzheimer’s, Parkinson’s, Huntington’s, and prion diseases, and also amyotrophic lateral sclerosis (ALS) present certain obvious similarities. Biometal microelements, such as copper, iron, manganese, and zinc, are crucial for many physiological functions, especially in the CNS. Shifts in the amounts of these metals are essential for the development and maintenance of numerous enzymatic activities, mitochondrial functions, neurotransmission, and also for memorization and learning. However, with deregulations in their homeostasis, particularly in those connected with redox activity, there are consequent changes in the ion and microelement balance. This redox activity may contribute to the production of free radicals that can react with various organic substrates, thus generating increased levels of oxidative stress. There is growing evidence that metal microelements play significant roles in the pathogenesis of neurodegenerative diseases. The interaction between metals and CNS proteins is crucial in the development or absence of neurodegeneration. In this way, homeostasis of metal microelements represents a mechanism of extreme importance. Our paper aims at an updated and critical review of the role of the respective metals in neurodegenerative diseases and the main related pathogenic mechanisms.